Carbon Sequestration with Forestry and Land-use/Cover Change: an Overview - Rai, S. C.; Sharma, P. (Indian Forester, 2003)
Conversion of land from forest to other usage is a threat to land-use sustenance and contributes negatively to climate change. Land-use/cover changes have caused a significant release of CO2 to the atmosphere from the terrestrial biota and soils. Soil is a major source of atmospheric CO2 , In the event of growing threats of global warming due to greenhouse gas emissions , reducing CO2 emission by sequestering C in the soil is of prime importance. Adoption of C sequestration measures in the soil can considerably reduce the rise in atmospheric CO2 level. Practices such as improved crop productivity and conservation tillage may be warranted to mitigate their carbon sequestration benefits. The purpose of this paper is to present an overview of measured rates of soil respiration from land-use/cover change to define the annual global CO2 flux.